2019
DOI: 10.5194/essd-11-603-2019
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of radiosonde humidity observations based on the Integrated Global Radiosonde Archive

Abstract: Abstract. Radiosonde measurements from the 1930s to present give unique information on the distribution and variability of water vapor in the troposphere. The sounding data from the Integrated Global Radiosonde Archive (IGRA) Version 2 are examined here until the end of 2016, aiming to describe the completeness of humidity observations (simultaneous measurements of pressure, temperature, and humidity) in different times and locations. Upon finding the stations with a non-negligible number of radiosonde observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
(116 reference statements)
1
17
0
Order By: Relevance
“…Table 2 confirms the low number of measurements available in the Southern Hemisphere (SH), although it is already known that the quantity of measurements alone cannot address the value of the dataset for a specific study without a representativeness study (Weatherhead et al, 2017). Further in-depth statistical analysis of the IGRA Version 2 historical times series and their temporal and spatial coverage at different pressure levels is available in Durre et al (2018) and in Ferreira et al (2019), the latter for relative humidity observations only. Another statistical analysis of the missing data and of their spatial coverage is provided in Sy et al (2020).…”
Section: Data Sources Usedsupporting
confidence: 55%
“…Table 2 confirms the low number of measurements available in the Southern Hemisphere (SH), although it is already known that the quantity of measurements alone cannot address the value of the dataset for a specific study without a representativeness study (Weatherhead et al, 2017). Further in-depth statistical analysis of the IGRA Version 2 historical times series and their temporal and spatial coverage at different pressure levels is available in Durre et al (2018) and in Ferreira et al (2019), the latter for relative humidity observations only. Another statistical analysis of the missing data and of their spatial coverage is provided in Sy et al (2020).…”
Section: Data Sources Usedsupporting
confidence: 55%
“…During 2009−19, radiosondes were regularly launched once per day, at 1200 UTC, at Neumayer station (which is also local time), and twice per day, at 0000 and 1200 UTC, at Syowa station (local time UTC+3). According to Ferreira et al (2019), Neumayer and Syowa stations have an acceptable completeness of radiosonde observations for our analysis. Because of the low temporal resolution of regular radiosonde observations and reduced vertical resolution available via IGRA2, these data can be used only for detecting large-scale features and not for detailed analysis of small-scale variability.…”
Section: Igra2mentioning
confidence: 99%
“…For instance, as we mentioned above, missing data are an intrinsic dataset characteristic due to a lack of continuity in operations contingently occurring at each measuring station. Although the completeness of historical radiosounding observations is improving over the years (Ferreira et al ., 2019), missing data in the time series are still frequent. This implies that, to provide a reliable assessment of the uncertainties affecting the estimation of trends using radiosounding data, the separate roles of temporal and spatial sampling effects due to the missing data must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Among the list of stations available from the IGRA data repository, a substantial subset of globally distributed radiosounding stations (656 stations) was used in this paper (Figure 1), namely, those with metadata available since 2000 to present. Ferreira et al (2019) found that the total number, spatial distribution and temporal completeness of IGRA stations vary considerably over the years due to several factors, and the number of vertical levels and the vertical extent in radiosonde reports depend on the standard and mandatory pressure levels provided according to the World Meteorological Organization (WMO) recommendations (WMO, 1996) to the Met services, as well as on the number of reported significant levels. Finally, due to various reasons, missing data are frequently found.…”
Section: Radiosonde Datasetsmentioning
confidence: 99%